2020
DOI: 10.1002/ejsp.2696
|View full text |Cite
|
Sign up to set email alerts
|

Country‐level and individual‐level predictors of men's support for gender equality in 42 countries

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 67 publications
(86 reference statements)
2
38
0
2
Order By: Relevance
“…In contrast to previous research that reported lower levels of perceived NR in females mostly from Middle Eastern countries (Eshel et al, 2020), the current study found that Filipino females had similar levels of NR with males. This finding attests to the Philippines having the smallest gender gap in the Asian region notably in the areas of leadership, economic participation and opportunity, and professional and technical positions (Kosakowska-Berezecka, Besta, Bosson, Jurek, & Zukauskiene, 2020;World Economic Forum, 2019)-all of which can boost NR.…”
Section: Antecedents Of Nrmentioning
confidence: 89%
“…In contrast to previous research that reported lower levels of perceived NR in females mostly from Middle Eastern countries (Eshel et al, 2020), the current study found that Filipino females had similar levels of NR with males. This finding attests to the Philippines having the smallest gender gap in the Asian region notably in the areas of leadership, economic participation and opportunity, and professional and technical positions (Kosakowska-Berezecka, Besta, Bosson, Jurek, & Zukauskiene, 2020;World Economic Forum, 2019)-all of which can boost NR.…”
Section: Antecedents Of Nrmentioning
confidence: 89%
“…The perception that intergroup relations is a zero-sum game, whereby gains for one group imply losses for other groups (e.g., Esses et al, 1998;Ruthig et al, 2017), as opposed to a positive-sum game (e.g., Deutsch, 2006), decreases advantaged groups' support for actions and policies benefitting disadvantaged groups (e.g., Radke et al, 2018). Two papers in this special issue provide further empirical support for the generalizability of this effect both cross-culturally (Kosakowska-Berezecka et al, 2020), and across various contexts of social inequality, that is, racism, heterosexism (Stefaniak et al, 2020), and sexism (Kosakowska-Berezecka et al, 2020). The reason why endorsing zero-sum beliefs represents a barrier to the advantaged group's engagement is because these beliefs are linked to fear about losing their privileged status (Stefaniak et al, 2020), and more hostile attitudes towards the disadvantaged group (Kosakowska-Berezecka et al, 2020).…”
Section: Advantag Ed G Roups' Per S Pec Tive On Allys Hipmentioning
confidence: 93%
“…that is by what other group members approve of (i.e., injunctive norms), and what they do (i.e., descriptive norms). Using a social network analysis approach, Roblain and colleagues 2020 Altogether, these papers illuminate new pathways for advantaged groups' potential involvement in allyship: perceptions of intergroup relations as interdependent and not antagonistic (Kosakowska-Berezecka et al, 2020;Stefaniak et al, 2020), meta-beliefs or expectations to be perceived as allies by disadvantaged groups (Adra et al, 2020), and egalitarian peer group norms (Roblain et al, 2020). They also deepen our knowledge about potential barriers to allyship, which seem to be particularly strong among highly identified advantaged group members.…”
Section: Advantag Ed G Roups' Per S Pec Tive On Allys Hipmentioning
confidence: 99%
See 2 more Smart Citations